Seroprevalence of dengue virus infection in Pune City in India, 2019: A decadal change - Kalichamy Alagarasu; Shilpa Tomar; Jayashri Patil; Rupali Bachal; Reva More; Minal Bote; Mahadeo Kakade; Vasanthy Venkatesh; Deepti Parashar; Babasaheb V. Tandale (Journal of Infection and Public Health, 2023)
Background: The burden of dengue infection needs to be monitored along with tracking of the changes in dengue virus (DENV) transmission intensity for vaccine introduction decisions. Methods: The seroprevalence of dengue was investigated in Pune City in India, in early 2019 using 1654 sera from apparently healthy human participants enrolled randomly through multistage cluster sampling. We used 797 retrospective human sera from late 2009 for comparison. All sera were assessed for the presence of dengue-specific IgG antibodies. A subset (n = 230) was tested for serotype-specific plaque reduction-neutralizing antibodies against all four serotypes. Results: The dengue IgG seroprevalence of 62.9% (95% CI 59.4–66.1) in 2009 increased to 88.4% (95% CI 86.8–89.8) in 2019. Age-stratified dengue seroprevalence revealed a gradual increase in IgG seropositivity from 70.1% in 0–9 years to 85.0% in 10–19 years. The annual probability of dengue infection estimated as a force of infection was 4.1 (95% CI 3.8–4.5) in 2009, which increased to 10.9 (95% CI 10.2–11.6) in 2019. Analysis of dengue serotype-specific neutralizing antibodies revealed DENV-3 as the dominant serotype. The age of exposure to at least one dengue serotype was reduced in 2019 over 2009. Conclusions: There was a significant increase in the intensity of dengue virus transmission in Pune City over the decade. Since over 85% of the participants above nine years of age had exposure to DENV by 2019, dengue vaccine introduction can be considered. Moreover, such repeated serosurveys in different regions might inform about the readiness of the population for dengue vaccination.